A comparative study of the level of some physical fitness elements with international standards for players of the amateur swimming club in M’Sila - chwia, boudjemaa; Belkheir, Abdelkader; belbar, Said (sports creativity, 2025)
The importance of physical fitness is highlighted in our modern era by the human need for it across all age groups. Technological advancements have led to numerous changes in lifestyles and behaviors, resulting in a fast-paced lifestyle in all aspects of life. This has been reflected in the culture of fast food and the widespread use of transportation. Reliance on technology and mechanization has increased significantly in most areas of life. All of this has led to a decline in physical activity, with individuals becoming sedentary and enslaved by leisure and luxury (Al-Hazzaa, 2000; Alwan, 1993). This has resulted in the emergence of several diseases associated with these changes, now known as hypokinetic diseases or diseases of socio-cultural change.